2008
DOI: 10.1002/jclp.20540
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming our resistances to “Doing” evidence‐based group practice: a commentary

Abstract: This commentary focuses on how the articles in the group therapy issue of the Journal of Clinical Psychology: In Session can address the resistances that many group practitioners exhibit to "doing" evidence-based practice (EBP). The articles attempt to overcome the resistances to practicing evidence-based group therapy through a process of education and skills training. A major issue cutting across the articles is the narrow focus of incorporating empirical findings only from studies specifically examining psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…In addition, future research could evaluate if group members, whose scores on the GSQ predict them to be poor group candidates, would respond to interventions designed to improve their skill in group processes or enhance their outcomes. Because of the short nature of the GSQ, one of the CORE-R battery of measures endorsed by the AGPA (Strauss et al, 2008), and its ease of administration, further studies demonstrating the predictive capabilities of this measure could help to reduce the resistance of group therapists to employing evi-dence-based practices (EBPs) in their group treatment (Kivlighan, 2008). Beecher (2008) indicated that resistance to employing EBPs in group practices may be reduced by measures like the GSQ contributing more valuable information and clinical utility and by increasing the benefit side of the cost benefit analysis clinicians perform when deciding which EBPs to employ in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, future research could evaluate if group members, whose scores on the GSQ predict them to be poor group candidates, would respond to interventions designed to improve their skill in group processes or enhance their outcomes. Because of the short nature of the GSQ, one of the CORE-R battery of measures endorsed by the AGPA (Strauss et al, 2008), and its ease of administration, further studies demonstrating the predictive capabilities of this measure could help to reduce the resistance of group therapists to employing evi-dence-based practices (EBPs) in their group treatment (Kivlighan, 2008). Beecher (2008) indicated that resistance to employing EBPs in group practices may be reduced by measures like the GSQ contributing more valuable information and clinical utility and by increasing the benefit side of the cost benefit analysis clinicians perform when deciding which EBPs to employ in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Una apuesta que tiene la ventaja añadida de estrechar y aunar sensibilidades, históricamente dispares, entre la investigación básica y la aplicada, entre el ámbito académico y el profesional. Unas dicotomías que los nuevos planes de integración y globalización tienen que ir erradicando de los planes de estudio y los programas y diseños de intervención (Kazdin, 2008;Kivlighan, 2008;Silverstein y Auerbach, 2009).…”
Section: Nuevas Orientaciones Y Agenda En Psicología De La Saludunclassified
“…In recommending this series for counsellors, I thought it useful to re-visit what Prochaska and Norcross (2007) considered to be one of the most important professional issues of the decade; the development of evidence-based practice in mental health. In looking to medically-based articles, I was also influenced by Kivlighan's (2008) comment on group therapists' resistance to using evidence-based research in their practice. He suggested that 'incorporating research from the whole field of group dynamics can increase the empirical basis for evidence-based practice', p.1284 [my emphasis].…”
Section: Introductionmentioning
confidence: 99%